Raters' L2 background as a potential source of bias in rating oral performance. (April 2013) - Winke, Paula; Gass, Susan; Myford, Carol
Based on evidence that listeners may favor certain foreign accents over others (Gass & Varonis, 1984; Major, Fitzmaurice, Bunta, & Balasubramanian, 2002; Tauroza & Luk, 1997) and that language-test raters may better comprehend and/or rate the speech of test takers whose native languages (L1s) are more familiar on some level (Carey, Mannell, & Dunn, 2011; Fayer & Krasinski, 1987; Scales, Wennerstrom, Richard, & Wu, 2006), we investigated whether accent familiarity (defined as having learned the test takers' L1) leads to rater bias. We examined 107 raters' ratings on 432 TOEFL iBT TM speech samples from 72 test takers. The raters of interest were L2 speakers of Spanish, Chinese, or Korean, while the test takers comprised three native-speaker groups (24 each) of Spanish, Chinese, and Korean. We analyzed the ratings using a multifaceted Rasch measurement approach. Results indicated that L2 Spanish raters were significantly more lenient with L1 Spanish test takers, as were L2 Chinese raters with L1 Chinese test takers. We conclude by concurring with Xi and Mollaun (2009, 2011) and Carey et al. that rater training should address raters' linguistic background as a potential rater effect. Furthermore, we discuss the importance of recognizing rater L2 as a possible source of bias.